Investigation of dispute factors and effects on construction projects arising from COVID-19 pandemic as a force majeure event - Aladag, Hande; Demirdogen, Gokhan; Isik, Zeynep (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
The Covid-19 pandemic has shown its effects not only in public health and economy but also in numerous industries including construction industry. In this sense, construction companies might face serious troubles such as disruptions in production activities in the supply chain, deterioration in cash flow, non-fulfillment of contract obligations due to Covid-19. Therefore, this study aims to investigate the effects of Covid-19 on the Turkish construction projects in terms of contractual relations between the parties of construction projects. Within this aim, data were gathered from 173 construction projects and then analyzed with Structural Equation Modeling (SEM) method. Results of the SEM analysis show that key dispute factors are progress payments, failure in claim notifications of contractors within the relevant period following the occurrence of pandemic in written form and failure in implementing quality monitoring and control processes due to lack of personnel with the highest factor loadings in their clusters.
Keywords: Construction industry; Covid-19; dispute management; force majeure; structural equation modeling (SEM); Engineering